People Management Highlighting Futures - Dias, Diana; Magalhães, Carla (Business, Management and Economics, 2023)
Managing people is the chief task of human resources officers in businesses and industries worldwide. It is a difficult and demanding task, especially in this era of highly dynamic and constantly changing business environments. In addition, the COVID-19 pandemic led to major and perhaps irreversible changes in how people work and how businesses operate. This book provides a comprehensive overview of what it means to manage people in the modern world. It includes sixteen chapters organized into three sections: "People Management in a VUCA World", "A Bright Future for People Management", and "People Management for People Happiness". Chapters address such topics as dealing with staff turnover, human resource development strategies during and post-crisis, diversity management, the relationship between career development and value proposition, the happy-productive worker thesis (HPWT), and much more.